Data Descriptor: A genome-scale RNAi screen for genetic interactors of the dynein co-factor nud-2 in Caenorhabditis elegans - Rocha, H (2018)
Cytoplasmic dynein 1 (dynein) is the predominant microtubule minus end-directed motor in animals and participates in a wide range of cellular processes, including membrane trafficking, nuclear migration, and cell division. Dynein's functional diversity depends on co-factors that regulate its subcellular localization, interaction with cargo, and motor activity. The ubiquitous co-factor nuclear distribution gene E (NudE) is implicated in many of dynein's functions, and mutations in NudE cause the brain developmental disease microcephaly. To identify genetic interactors of the Caenorhabditis elegans NudE homolog nud-2, we performed a genome-wide RNAi screen with the null allele nud-2(ok949), which compromises dynein function but leaves animals viable and fertile. Using bacterial feeding to deliver dsRNAs in a 96-well liquid format and a semi-automated fluorescence microscopy approach for counting parents and progeny, we screened 19762 bacterial clones and identified 38 genes whose inhibition caused enhanced lethality in nud-2(ok949) relative to the nud-2(+) control. Further study of these genes, many of which participate in cell division, promises to provide insight into the function and regulation of dynein.